PERANAN ORANGTUA DAN GURU DALAM PEMBERDAYAAN ANAK BERKELAINAN - Tri Mulyani (Jurnal Cakrawala Pendidikan, 2001)
The discussion about parent and teacher's role in the handicapped child empower, is limited only for the sight-impaired child, hearing impaired child, and the autism. This case is discussed based on the researcher's experience and the result ofthe research shows that parent and teacher role is very strategy in reaching the goal in the handicapped child's empowerment in social adjustment and independent life. Handicapped child's empowerment will be effective and efficient if parent and teacher becomes pioneer in changing from negative attitude to positive attitude to the handicapped child. In fact negative attitude in the society first appears from the parent of the handicapped child: Experience shows that parent who has no experience with his/herhandicapped child, in general will be shocked, hide the child, also deny the child! the child existantion guessing that the child has no potention, so that will delay the child's progress. The effort to realize parent and teacher positive' attitude, in order, to empower the handicapped child can reach optimally so the research and socializing education services for the handicapped child must be intensive. Multi discipline cooperation, for example with the psycholog, or the paedagog, therapy expert and the other expert who concern to the handicapped child. Trough the increasing cooperation'" with the 'other side." hoping learning process and empower for the handicapped child (especially the sight impaired child, the hearing impaired child and the autism) will be deve)opsamewith the individual ,child potention.